Non- $$D{\bar{D}}$$ D D ¯ decays into light meson pairs of the D-wave charmonium $$ψ _3(3842)$$ ψ 3 ( 3842 ) - Zi-Yue Bai; Bao-Jun Lai; Qin-Song Zhou; Xiang Liu (European Physical Journal C: Particles and Fields)
Abstract As a D-wave partner of $$ψ (3770)$$ ψ ( 3770 ) identified by the LHCb Collaboration, $$ψ _3(3842)$$ ψ 3 ( 3842 ) lies between the $$D{\bar{D}}$$ D D ¯ and $$D\bar{D^*}$$ D D ∗ ¯ thresholds. Its non- $$D{\bar{D}}$$ D D ¯ decay channels have attracted considerable interest. In this study, we investigate these allowed non- $$D{\bar{D}}$$ D D ¯ decays of $$ψ _3(3842)$$ ψ 3 ( 3842 ) into PP, PV, and VV final states using the hadronic loop mechanism, where P and V represent light pseudoscalar and vector mesons, respectively. Our results suggest that these non- $$D{\bar{D}}$$ D D ¯ decays of $$ψ _3(3842)$$ ψ 3 ( 3842 ) can be significant, with contributions primarily driven by hadronic loops. Notably, the $$ρ π $$ ρ π channel stands out as the main non- $$D{\bar{D}}$$ D D ¯ decay mode, while non- $$D{\bar{D}}$$ D D ¯ decay channels involving strange mesons are also sizable. These predictions could be tested in future experiments such as those at LHCb and BESIII.